Ex-situ soft X-ray absorption spectroscopic investigation of NiCo2O4 annealed in different gases for hydrogen generation by electrolysis of urea. (14th June 2019) - Chang, Han-Wei; Dong, Chung-Li; Lu, Ying-Rui; Huang, Yu-Cheng; Chen, Chi-Liang; Chen, Jeng-Lung; Chen, Jin-Ming; Lee, Jyh-Fu; Tsai, Yu-Chen
Abstract: Electrochemical and ex-situ X-ray absorption spectroscopic (XAS) measurements of NiCo2 O4 that have been annealed in different gases (Ar and air) were made to evaluate the efficiency of its electrocatalysis of hydrogen generation by the electrolysis of urea. The electrochemical and XAS measurements demonstrated that NCO–Ar contain significant amounts of Co 2+ in octahedral coordination was more favorable than NCO-air for urea electrolysis owing to the effective exposure of electrochemical active sites to participate in the Faradic redox reaction. Further insight into the electrocatalytic mechanism of NiCo2 O4 -based materials during urea electrolysis was obtained using ex-situ soft XAS. The results of ex-situ soft XAS revealed that the variation of the octahedral and tetrahedral coordinations of Co 2+ in NCO–Ar and NCO-air importantly contributes to electrocatalytic behavior. NCO–Ar exhibits excellent electrocatalytic activity towards the Co redox couples in a repetitive cycling process owing to the creation of highly efficient active sites (octahedral Co 2+ ). This study presents importantly x-ray spectroscopic determination of the change in electronic structure of catalyst for hydrogen production. Graphical abstract: Image 1 Highlights: Electronic structure of NiCo2 O4 for urea electrolysis studied by XAS. Varied octahedral and tetrahedral Co 2+ in NiCo2 O4 annealed with different gases. High electrocatalytic activity of NiCo2 O4 annealed in Ar due to active Co 2+ .